PEMBERDAYAAN MANAJEMEN UMKM PASCA PANDEMI COVID-19 SEBAGAI UPAYA PENINGKATAN DAYA SAING USAHA - Nailariza Umami; Maria Agatha Sri Widyanti Hastuti; Muhammad Anasrulloh; Aldila Septiana (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
The world is currently facing the COVID-19 pandemic. The COVID-19 pandemic has had an economic, social and political impact, not only on major countries but almost all countries in the world. The small economic sector or what we know as MSMEs (Micro, Small and Medium Enterprises) is pioneered by small communities, especially those in rural areas. A study stated that Covid-19 caused Indonesia to experience a decrease in the percentage of economic growth by 0.1% in 2020. In general, the following are the real impacts caused by Covid-19 on the SME sector in Indonesia. Community service which was carried out in collaboration with UPN Veterans Surabaya KKN students located in the Klampok Blitar sub-district, was carried out with the aim of inviting MSMEs to bounce back after this pandemic by taking the first step in the form of strengthening business management. In this business management there are several main things, namely production management, marketing management, human resource management and financial management. The four are a unit that must be managed together well, so that it can strengthen the establishment of a business. The socialization was attended by 36 business actors in Klampok Village, Blitar City. The approach used to implement this method uses the lecture method, question and answer, games (Role Playing), giveaway distribution and reflection (evaluation). From the evaluation results, the implementation of the socialization was very successful. The number of invited participants in attendance exceeded the number of invitees. And the enthusiasm of MSME actors is seen by their activeness in asking questions because of their high curiosity. In fact, most of the socialization participants wanted a similar event to be held on an ongoing basis.